PROBLEMS OF RELIABILITY OF FOUNDATIONS AND FOUNDATIONS ON SALINE SOILS - Makhsimov Kasimkhan Ibaevich (Journals Park Publishing, 2024)
The influence of aggressiveness and variability of the properties of saline soil on the work of foundations and bases is studied. Materials with non-corrosive properties are presented, including electrokinetic stabilization that reduces the salt content in soils and increases its bearing capacity.
Keywords: Saline soils, suffusion, concrete corrosion, fiber polymers, electrokinetic stabilization, protective coatings.